2010
DOI: 10.1055/s-0030-1255110
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Approach to Assess VT During a Field Walk Test

Abstract: We aimed to examine whether the ventilatory threshold (VT) during an incremental shuttle walk test (ISWT) could be determined using heart rate variability (HRV) analysis. Further aims were to assess variables capable of predicting performance in the ISWT and the intensity of this test. Beat-to-beat RR intervals and gas exchange values in 10 healthy subjects (31-83 years; 7 men) were collected during the ISWT. The ventilatory equivalent was used to assess VT from respiratory components. To determine the HRV thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 30 publications
4
55
0
3
Order By: Relevance
“…The present data are consistent with previous studies that found a significant, strong correlation between GET and HRVT within maximal CPET (11,14-16). In fact, our data showed that SD1 stabilization occurred at intensities corresponding to ∼52, 53, and 56% V˙O2 peak for cycling, walking, and running CPETs, which in turn are in agreement with the findings of previous studies that verified a progressive decrease followed by a stabilization of SD1 until ∼50-66% V˙O2 peak (11,17,19).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present data are consistent with previous studies that found a significant, strong correlation between GET and HRVT within maximal CPET (11,14-16). In fact, our data showed that SD1 stabilization occurred at intensities corresponding to ∼52, 53, and 56% V˙O2 peak for cycling, walking, and running CPETs, which in turn are in agreement with the findings of previous studies that verified a progressive decrease followed by a stabilization of SD1 until ∼50-66% V˙O2 peak (11,17,19).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, this method of analysis was chosen because it uses the same type of visual technique that was applied to determine GET (see Figure 1), being relatively simple to use and understand (32). Previous studies have adopted the SD1 as a criterion for determining the HRVT (14-17), because this index seems to be related to parasympathetic activity and the HRVT assessment has been mainly attributed to vagal withdrawal (11). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(24) However, on the 6MWT, the pace is controlled by the subject and an aerobic steady state is achieved. (25) This suggests that the exercise intensity is at or below the lactate threshold in most cases, which results in a lower demand for glycolytic muscle fiber recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…The significant vagal withdrawal during incremental exercises has been well documented in the literature using time domain HRV analysis (4,18,23 (4) which used similar visual analysis to identify the vagal withdrawal, that is the point at which the HRV showed no further decrease. However, it is important to note that in contrast to the present study which used a treadmill running incremental test, Karapetian et al (4) used a cycle ergometer, thus limiting deeper comparisons as the values were expressed as power output (watts) instead of speed (km.h -1 ).…”
Section: Hrv Data Set and The Identification Of Lactate Thresholdsmentioning
confidence: 99%